Вы находитесь на странице: 1из 24

.

16 2012

f (x, y )
(x0 , y0 ),
f
y (x0 , y0 ).
f (x, y ) .

f
x


:
z = f (x, y ), x = (t), y = (t)
z = f ((t), (t)).

,

dz
f dx
f dy
= fx0 (x, y )0 (t) + fy0 (x, y ) 0 (t) =
+
.
dt
x dt
y dt
. z = xy 2 , x = cos t, y = sin t.
zt0 = y 2 ( sin t) + 2xy cos t.
.



, ,
z = f (u, v ), u = u(x, y ), v = v (x, y ),


z
z u
z
=
+
x
u x
v
z
z u
z
=
+
y
u y
v

v
,
x
v
.
y

F (x, y ) = 0,
y = f (x) .
F (x, f (x)) = 0,
Fx0 (x, y ) 1 + Fy0 (x, y )f 0 (x) = 0.

y 0 = f 0 (x) =

Fx0 (x, y )
.
Fy0 (x, y )

z = f (x, y ) M0 (x0 , y0 ),
( l)
s = ai + bj. z


dz
z
= lim
,
l0 l
dl
l l,
z = f (x, y ) f (x0 , y0 ).

l M
M0

s
x



x = x0 + t cos , y = y0 + t cos ,
, s Ox Oy
. t l
dz
dz

=
,
dl
dt


dz
= zx0 x 0 + zy0 y 0 = zx0 cos + zy0 cos
dt
,
(cos , cos ) =

1
1
s=
(ai + bj).
|s|
a2 + b 2

A = zx0 (x0 , y0 ), B = zy0 (x0 , y0 ). G = Ai + Bj.


,
dz
= A cos + B cos = G s0 = |G| cos ,
dl
s0 l, G
l. ,
G,
. G grad z
grad z = G = zx0 i + zy0 j.


.
z = ax + by + c grad z = (a, b), ..
ax + by + c = C. grad z = (A, B)
(x0 , y0 ). A(x x0 ) + B(y y0 ) = 0.
.
,
z = C, C = f (x0 , y0 ).

f (x, y ) = C (x0 , y0 ) (
)
fx0 (x0 , y0 )(x x0 ) + fy0 (x0 , y0 )(y y0 ) = 0.

u = f (x, y , z)
(x, y , z),
R3 .
,

p
u = R 2 x 2 y 2 z 2 R
.
, ,
.

.
u = C f (x, y , z) = C.

f (x, y , z) M0 (x0 , y0 , z0 )
M0 ,

f (x, y , z) = u0 + A(x x0 ) + B(y y0 ) + C(z z0 )
q
+ (x x0 )2 + (y y0 )2 + (z z0 )2 ,
u0 = f (x0 , y0 , z0 ), 0, x x0 , y y0 , z z0 .
, M0
A = ux0 , B = uy0 , C = uz0


du = ux0 (x x0 ) + uy0 (y y0 ) + uz0 (z z0 ) = ux0 dx + uy0 dy + uz0 dz.

z = f (x(t), y (t), z(t)),
du
u dx
u dy
u dz
=
+
+
dt
x dt
y dt
z dt

.
f (x, y , z)
s = (a, b, c) M0 (x0 , y0 , z0 ), l
u
u
u
du
=
cos +
cos +
cos
dl
x
y
z

du
= grad u s0 = |grad u| cos ,
dl

grad u = (ux0 , uy0 , uz0 ),


s0 =

(a, b, c)
1
s=
= (cos , cos , cos )
2
|s|
a + b2 + c 2

,

f (x, y , z) = C M0 (x0 , y0 , z0 )
fx0 (x0 , y0 , z0 )(x x0 ) + fy0 (x0 , y0 , z0 )(y y0 )
+ fz0 (x0 , y0 , z0 )(z z0 ) = 0.